Developing the student worksheet with problem-solving approach to improve critical thinking skills and the concept understanding of physics - Trisnowati, Eli; Sumardi, Yosaphat (Momentum: Physics Education Journal, 2019)
The study aimed to investigate the quality of the developed student worksheet with a problem-solving approach in line to the determined criteria and the improvement of students’ critical thinking skills and the conceptual understanding of physics by implementing the student’s worksheet. This study was a research and development study by applying the development model by Borg & Gall. The try out subjects of validation product were students of grades X and XI of MAN (Islamic High School) Yogyakarta III. The data collection techniques used validation sheets, observation sheets, evaluation sheets of student’s worksheet, and tests. The product of this research was student’s worksheet with a problem-solving approach on the topic of optical instruments for grade X of senior high school. The evaluation of student’s worksheet by experts, teachers, peer reviewers, and students are at the best categories for learning, construct, and technical aspects. The gained standard score of students’ conceptual understanding and students’ critical thinking skills for grade X who learned through student’s worksheet with a problem-solving approach, called treatment class, were higher than students who learned without student’s worksheet with a problem-solving approach, called control class.